Pemberdayaan masyarakat di Desa Balai Makam dalam pemanfaatan bonggol pisang sebagai rintisan Usaha Mikro Kecil Menengah (UMKM) - Tetty Marta Linda; Sezhianindi Firiola; Rahmah Agnissah; Binar Robinson M; Muhammad Rinaldi; Sri Ramadhani (Unri Conference Series: Community Engagement, 2020)
Banana hump is one part of the banana plant that is still very rarely used. The Banana hump can be an item with a selling value because it contains high carbohydrates, fiber, and calcium to be an alternative food ingredient. The banana hump can be turned into nutrient-rich flour. Community empowerment to process banana hump into something useful and can be a pilot business for residents is one of the keys to this success of this activity. This service will provide benefits to various parties, including for community service participants, for the counseling implementation team, for universities, and for the government. The purpose of this activity is to introduce and train the skills of making flour made from banana humps, which we named "Tebosang" for the community of Balai Makam Village, Bathin Solapan District, Bengkalis Regency. The methods used include site surveys, interactive training preparation, mentoring, monitoring, and evaluation. Making flour from banana hump started with a waste of old banana hump, cleaned the surface, then sliced thin approximately 0.5 cm. The hump then washed and then soaked with whiting for about one hour, then rinsed and dried. The dried hump slices are then blended and then sifted so that they become flour. The community's enthusiasm was relatively high at the time of the training, shown by the community's involvement at the demonstration. The monitoring and evaluation results show that the community already understands how to make flour from the banana hump. The result also showed that the village community is already producing "tebosang" flour, which has commercial potential, a start-up for micro, small and medium enterprises in each community.